The Potential Differential Impact of PRL and MIR4760 Gene Expression in Patients with PCOS and Hyperprolactinemia: A Pilot Study - Ali, Amal Mohammed; Lafta, Fadhel Mohammed; Abed, Dina Wael; Almukhtar, Asmaa Amer (Iraqi Journal of Science, 2026)
Polycystic ovary syndrome (PCOS) is the most prevalent endocrinopathy affecting reproductive-aged females, in which prolactin (PRL) hormone seems to significantly affect the disease’s course. Considering the scarcity of local studies investigating the potential association of MIR4760 expression in the context of POCS and hyperprolactinemia, the present study aims to assess the potential differential value of PRL and MIR4760 gene expression in hyperprolactinemia and POCS patients. A total of 75 females (age range 14-40 years) were involved in this study (including 25 patients diagnosed with POCS, 25 patients with hyperprolactinemia, and 25 apparently healthy controls). Peripheral blood samples were collected from each of the assessed participants for prolactin serum estimation and RNA extraction. PRL and MIR4760 relative gene expression was assessed utilizing the qPCR technique, while prolactin serum levels were estimated using the Human PRL (Prolactin) ELISA Kit. The results showed significant elevation (P=0.001) in the expression of PRL gene in patients with hyperprolactinemia and PCOS in comparison to healthy controls (expression fold =3.27 and 1.27, respectively). While the expression of MIR4760 was reduced significantly (P=0.001) in the investigated patients groups (hyperprolactinemia and PCOS) compared to healthy controls. The present study exhibited significantly increased (P≤0.001) prolactin serum levels (P≤0.001) in the PCOS and hyperprolactemia patients in comparison to those of the healthy controls (36.46±4.86, 40.46 ± 15.06, and 19.76±5, respectively). Overall, the present study findings support the assumption that links PRL overexpression to PCOS pathogenicity. Additionally, the expression of PRL levels seems to be negatively associated with MIR4760 expression status in the investigated group of POCS patients.